2023
DOI: 10.1002/alz.13035
|View full text |Cite
|
Sign up to set email alerts
|

Social enrichment on the job: Complex work with people improves episodic memory, promotes brain reserve, and reduces the risk of dementia

Abstract: Individuals with more complex jobs experience better cognitive function in old age and a lower risk of dementia, yet complexity has multiple dimensions. Drawing on the Social Networks in Alzheimer Disease study, we examine the association between occupational complexity and cognition in a sample of older adults (N = 355). A standard deviation (SD) increase in complex work with people is associated with a 9% to 12% reduction in the probability of mild cognitive impairment or dementia, a 0.14–0.19 SD increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…42 According to cognitive reserve theory, greater occupational skill complexity across the lifetime should help to protect later-life cognitive function from accumulating aging-related brain pathology or injury. 42 However, we observed heterogeneity in associations across our countries under study, and some prior studies have observed null associations, mixed associations across different types of occupational skill or cognitive function domains, 18,[22][23][24] or even faster rates of cognitive decline over time with greater occupational complexity. 21 Variations in the measurement and definition of occupational skill across studies may further contribute to inconsistencies in associations.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…42 According to cognitive reserve theory, greater occupational skill complexity across the lifetime should help to protect later-life cognitive function from accumulating aging-related brain pathology or injury. 42 However, we observed heterogeneity in associations across our countries under study, and some prior studies have observed null associations, mixed associations across different types of occupational skill or cognitive function domains, 18,[22][23][24] or even faster rates of cognitive decline over time with greater occupational complexity. 21 Variations in the measurement and definition of occupational skill across studies may further contribute to inconsistencies in associations.…”
Section: Discussionmentioning
confidence: 57%
“…The existing evidence on lifetime occupational skill and later‐life cognitive health outcomes is somewhat mixed, with most studies observing protective associations, 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 and others observing null, negative, or mixed associations across different types of skills and cognitive domains. 18 , 19 , 20 , 21 , 22 , 23 , 24 Most of this existing research is from high‐income countries, with the exception of a study in Brazil; much of it includes non‐population‐representative samples, and it does not capture the diversity of job types experienced around the world. Greater occupational skill complexity may not be uniformly associated with better later‐life cognitive outcomes across global populations.…”
Section: Introductionmentioning
confidence: 99%
“…Having a mentally stimulating job and engaging in other mentally stimulating activities may also help build cognitive reserve. [165][166][167][168][169][170] Other researchers emphasize the indirect effects of the number of years of formal education, such as its effects on dementia risk through socioeconomic status (SES). SES typically is defined as access to economic resources, including income, education, employment and occupation, but also includes factors such as financial security and perceived social standing.…”
Section: Educationmentioning
confidence: 99%
“…Having a mentally stimulating job and engaging in other mentally stimulating activities may also help build cognitive reserve. 165 , 166 , 167 , 168 , 169 , 170 …”
Section: Overviewmentioning
confidence: 99%
“…Each test required participants to learn and remember details from a story, words, and an image, respectively. Using standardized scoring procedures (Weintraub et al, 2018), overall scores were standardized for each task, then averaged together, commensurate with past work (M. E. Coleman et al, 2023). Importantly, this method has been shown to connect to social bridging networks (L. J.…”
Section: General Cognitive Functionmentioning
confidence: 99%